Dorea phocaeensis sp. nov., a new bacterium isolated from the stool of a healthy 29-year-old male. (November 2019) - Takakura, T.; Francis, R.; Anani, H.; Naud, S.; Raoult, D.; Bou Khalil, J.Y.
Abstract: Dorea phocaeensis strain Marseille-P4003 T (= CSURP4003 T ; = CCUG71359 T ) is a new species isolated from the stool of a healthy 29-year-old male from France.